FEASIBILITY OF INCORPORATING JACKFRUIT FOR THE DEVELOPMENT OF INSTANT PAYASAM MIX - K.H. AJISHA, C.L. SHARON, E.R. ANEENA, SEEJA THOMACHAN, SAJI GOMEZ and P.S LAKSHMY (The Journal of Research ANGRAU, 2022)
This study was conducted (2016-2018) to develop jackfruit based instant vermicelli payasammix by using jackfruit flour and jackfruit seed flour. Based on organoleptic evaluation, mean scoreswas high for vermicelli and payasam prepared with 70 % raw jackfruit flour and 30 % jackfruit seedflour with an overall acceptability of 8.55 and 8.57,respectively. The nutrient content of selectedjackfruit based vermicelli observed to have moisture (7.18 %), energy (284 Kcal 100g-1), carbohydrate(63.7g 100g-1), protein (3.4g 100g-1), fat (0.80g 100g-1) and fibre (3.9g 100g-1). The vermicelli wasrich in calcium (53mg 100g-1), iron (6.7mg 100g-1), sodium (18.14mg 100g-1) and potassium (242mg100g-1). An instant payasam mix was standardized usingthe selected jackfruit vermicelli along withsugar, nuts, raisins and flavourings. The jackfruit instant payasam mix had good sensory characteristicswith an overall acceptability was 8.62. The market potential of jackfruit can be promoted if the fruitsare made available to the consumer in a ready to cook form throughout the year.